Desentralisasi Penanggulangan HIV/AIDS: Studi Pada Pemerintah Daerah Kabupaten Tulungagung - Muhammad Akbar Nursasmita; Putri Langgeng Sari; Ahmad Ibnu Riza; Annisa Nurul Hakim (Kertha Wicaksana, 2026)
Decentralization of health governance places significant responsibility on local governments to address public health challenges, including HIV/AIDS, through context-sensitive and integrated policies. In Indonesia, particularly in Tulungagung Regency, East Java, despite the establishment of local regulations on HIV/AIDS prevention, a gap remains between the normative legal framework and its practical implementation at the local level. This study examines the decentralized HIV/AIDS response in Tulungagung, with particular attention to the absence of a Regent's Regulation as an implementing instrument for Regional Regulation No. 4 of 2021 concerning HIV/AIDS Prevention and Control. Using socio-legal research methods, this study combines legal analysis with sociological and policy approaches to examine how legal norms operate in practice. The findings indicate that despite the existence of a local legal framework, the absence of a Regent's Regulation as an implementing instrument has resulted in weak policy orchestration, limited intersectoral coordination, limited budgeting mechanisms, and reduced administrative accountability. These conditions undermine the effectiveness of decentralized HIV/AIDS governance and diminish the protection of the right to health for people living with HIV/AIDS. This study concludes that the formulation of Regional Head Regulations not only resolves normative problems and delegation of local regulations, more than that, it can be used as a mechanism for orchestrating cross-sector policies at the local level.